1994
DOI: 10.1111/j.1439-0388.1994.tb00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in inbreeding in Dutch Black and White dairy cattle

Abstract: The objective of this study was to estimate trends in inbreeding in Dutch Black and White dairy cattle. A pedigree file for 4 280 588 cattle born after 1965 was used. In the early 1970s, Holstein-Friesian was introduced, gradually replacing Dutch Friesian. Analyses were performed for all Dutch Black and White and original Dutch Friesian separately. Because of incompleteness of pedigrees, a reduced data set was created with only records for animals with complete pedigrees to 1975. Using the complete pedigree da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
1
10
0
2
Order By: Relevance
“…The frequency of inbreeding coefficients changed, as shown in Figure 2. In 1960, there were more than 80% non‐inbred animals; this trend is similar to that in the Jersey breed, as reported by M iglior et al (1992) and the Dutch Black and White dairy cattle, as reported be T e B raake et al (1994). The proportion decreased, and in 1970 only 20% of the animals were non‐inbred and none remained in 1980 and 1990.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The frequency of inbreeding coefficients changed, as shown in Figure 2. In 1960, there were more than 80% non‐inbred animals; this trend is similar to that in the Jersey breed, as reported by M iglior et al (1992) and the Dutch Black and White dairy cattle, as reported be T e B raake et al (1994). The proportion decreased, and in 1970 only 20% of the animals were non‐inbred and none remained in 1980 and 1990.…”
Section: Resultssupporting
confidence: 81%
“…The average inbreeding coefficient in the Japanese Brown in 1990 (5.43%) was higher than those reported for foreign breeds; examples include 3.25% for males and 3.62% for females in 1987 in Brazil Gir cattle (Q ueiroz and L ôbo 1993), 1.9% for bulls and 1.7% for cows born from 1986 to 1990 in the Canadian Holstein (M iglior and B urnside 1995), 5.3% in the Haflinger Horse, 2.3% in the Bavarian Draft Horse, 2.9% in the Trotter FRG Horse, 3.8% in the Brown Swiss, 4.1% in the US Holstein (all relative to populations c.1900, cited in P irchner 1983), 0.26% for bulls in the Brown Swiss in the USA (H udson and van V leck 1984), 2.0% in 1987 in the American Holstein ( van R aden 1992) and Δ F ST 0.2 esp. 0.1 in Dutch Black and White and Dutch Friesians per year (T e B raake et al 1994). The reasons for the high inbreeding coefficient in the Japanese Brown should be due to them being kept as a closed and small population for a long time.…”
Section: Resultsmentioning
confidence: 99%
“…The trend of inbreeding in a population should be estimated only when individuals have sufficient ancestral generations. In pedigrees as short as we have in Xalda sheep, in which individuals do not have sufficient ancestral generations, we could not obtain an accurate estimation of the trend of inbreeding ( Te Braake et al 1994) and, therefore, we could not obtain an accurate estimation of N e . The average F of the current Xalda population is 0.01762.…”
Section: Resultsmentioning
confidence: 93%
“…Traditional parameters based on inbreeding and effective size do not seem to be as effective as needed when we want to conserve the genetic makeup of a population that is not well established. When pedigree information is shallow, we underestimate the number of inbred individuals and the average inbreeding coefficient, but give relatively high inbreeding coefficients for inbred animals ( Te Braake et al 1994). Simon (1999) proposed the calculation of the maximum values of inbreeding in 50 years of conservation ( F g ) to classify the endangerment of a population.…”
Section: Discussionmentioning
confidence: 99%
“…Proportion of Holstein genes in British Holstein-Friesian bulls was 40% in 1992 but had risen to 57% in 1997 (Roughsedge et al 1999). In the Dutch black and white dairy cattle population the proportion of Holstein genes was nearly 80% in 1992 (Te Braake et al 1994). …”
Section: Volmentioning
confidence: 99%